Molecular basis of inherited thrombocytopenias. - Savoia, A (Clin Genet, 2015)
Inherited thrombocytopenias (IT) are a heterogeneous group of diseases caused by at least 20 different genes. At present, these genes account for approximately 50% of cases, suggesting that novel genes have yet to be identified for a comprehensive understanding of platelet biogenesis defects. This review provides an update of ITs focusing on the molecular basis and potential pathogenic mechanisms affecting megakaryopoiesis and platelet production.